The Effect of Problem-Based Learning Integrated Numbered Head Together on the Critical Thinking Ability of Grade XI Students - Aggraini, Meiza Dwi; Koto, Irwan; Gunawan, Bodi (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2024)
This study aims to examine the effect of physics learning with Problem Based Learning (PBL) integrated with Numbered Head Together (NHT) on critical thinking skills of XI students. This study adopted a quasi-experimental design with nonequivalent control group design. The total research sample was 66 students with 34 students as the experimental group and 32 students as the control group. The research data were tested through independent t-test to determine whether the treatment had a significant effect (Sig. 5%) on critical thinking skills (dependent variable). To determine the effect size of PBL integrated with NHT on the dependent variable, the effect size test was conducted. The research data were obtained through essay tests with five indicators of critical thinking according to Facione, namely the ability to think analysis, interpretation, inference, evaluation and explanation. The research findings are physics learning with PBL integrated NHT affects critical thinking skills that are statistically significant with Cohen's d effect size coefficient >0.8 (high category).